The Responsibilities of Influencer Doctors Promoting Skincare Products on Social Media - Amandha, Rendytha Khansa; Sugiyono, Heru (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
Influencer doctors are prohibited from promoting skincare products on social media as regulated in MKEK Decree 029/2021. This has pros and cons, where influencer doctors are considered to help people pay more attention to a skincare product before buying and it is feared that there will be excessive claims on a product because they have expertise in the field of beauty. This research aims to analyze the responsibilities of influencer doctors who promote skincare products on social media and legal protection for consumers who experience losses from the promotion of skincare products carried out by influencer doctors on social media through normative juridical research methods which are supported by primary, secondary, and tertiary data. The study shows that the responsibility of influencer doctors needs to be looked at further regarding the fulfillment of mistakes made, if they are not at fault, then full responsibility falls on the business actor. Meanwhile, if guilty, the influencer doctor can be subject to sanctions as regulated in the 2018 MKEK Guidelines and the Consumer Protection Law. The embodiment of consumer protection is to provide rights and obligations for consumers, business actors and advertising business actors. Consumers often think impulsively when buying skincare products because of other people's reviews. Therefore, to avoid losses, consumers need to be more careful when purchasing skin care products. If they experience losses, consumers can apply for compensation or peace efforts, in court and outside of court.Keywords: Responsibility, Consumer Protection, Influencer Doctors, Skincare